The Knowledge of Good Critique of Axiological Reason - Hartman, Robert S. (Hartman Institute Axiology Studies, 2021)
This book presents Robert S. Hartman's formal theory of value and critically examines many other twentieth century value theorists in its light, including A.J. Ayer, Kurt Baier, Brand Blanshard, Paul Edwards, Albert Einstein, William K. Frankena, R.M. Hare, Nicolai Hartmann, Martin Heidegger, G.E. Moore, P.H. Nowell-Smith, Jose Ortega y Gasset, Charles Stevenson, Paul W. Taylor, Stephen E. Toulmin, and J.O. Urmson.